2021
DOI: 10.3390/f12111450
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Biotic and Abiotic Factors and Diversity Determine Productivity in Natural Deciduous Forests

Abstract: The relative importance of different biotic and abiotic variables for estimating forest productivity remains unclear for many forest ecosystems around the world, and it is hypothesized that forest productivity could also be estimated by local biodiversity factors. Using a large dataset from 258 forest monitoring permanent sample plots distributed across uneven-aged and mixed forests in northern Iran, we tested the relationship between tree species diversity and forest productivity and examined whether several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…Therefore, the findings of our study suggest that, compared to other methods, the projection matrix model estimates allowable cut lower and closer to the net increment, and thus can prevent the possible consequences of harvest over increment of the single-selection method. Forest cutting is used as a tool for forest cultivation (biological production) and wood harvesting (mechanical production) and leads the forest toward desirable quantitative and qualitative production [50]. To use this tool properly, it is necessary to accurately estimate the allowable cut [51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings of our study suggest that, compared to other methods, the projection matrix model estimates allowable cut lower and closer to the net increment, and thus can prevent the possible consequences of harvest over increment of the single-selection method. Forest cutting is used as a tool for forest cultivation (biological production) and wood harvesting (mechanical production) and leads the forest toward desirable quantitative and qualitative production [50]. To use this tool properly, it is necessary to accurately estimate the allowable cut [51].…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic factors include genetic traits (Wang et al 2022), species characteristics (Pretzsch 2021) and physiological processes (Avanzi et al 2019) determining the tree's growth potential and ability to capture and allocate resources e ciently. Extrinsic factors encompass large-scale environmental factors such as climate and landscape characteristics and small scale factors such as soil nutrients and water availability for growth, development, and competition (Robertson 1992;Cienciala et al 2016;Chakraborty et al 2017;Bayat et al 2021). Additionally, disturbances such as re, wind, or insect outbreaks can have both negative and positive impacts on tree growth (Splechtna et al 2005;Szewczyk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research have shown that ecological and socio-economic factors have a significant effect on forest sustainability (Ouyang et al, 2021;Khan and Hou, 2021;Zahraee et al, 2020). Forests are dependent on various ecological factors, such as climate, soil, water availability, topography, and biotic factors like plant and animal species (Bayat et al, 2021). These factors play a crucial role in determining the health and productivity of forests and their ability to sustainably provide various environmental, economic, and social benefits (Raihan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%